Numerical analysis of seismic damage characteristics of an underground cavern intersected by a steeply dipped fault - CHEN Shi-jie; XIAO Ming; WANG Xiao-wei; CHEN Jun-tao (Rock and Soil Mechanics, 2021)
The steeply dipped fault zone is the weak link of the seismic stability of underground caverns. Aimed at the complex dynamic interaction characteristics between the surrounding rock and fault, based on the Ladanyi's shear strength model, the seismic deterioration coefficient was introduced, and a shear strength model considering nonlinear mechanical properties and seismic deterioration effect was established. Further considering the discontinuous deformation characteristics between surrounding rock and faults, a three-dimensional dynamic contact force method was proposed considering both the complex shear strength and multiple contact states. The method was applied to the Jinchuan underground powerhouse to study its seismic damage characteristics under the influence of the steeply dipped fault F31. The results indicate that after considering the interface and seismic deterioration effects, the seismic response of the cavern increases, the dislocation between the surrounding rock and fault is more evident, and a certain depth of separation and sliding failure zones occurs. The steeply dipped fault cuts the high sidewalls of the main workshop, and forms a weak zone where the surrounding rock thickness is thin. The weak zone has more significant deformation and damage, and is prone to flexural toppling deformation and slipping deformation into the cavern on the upstream and downstream sidewalls, respectively. The distribution of the sliding and separation failure zone of the interfaces between the surrounding rock and fault are dynamic changes during the seismic process, and it continues to extend to the deep. Among them, the separation zone is relatively large at the arch abutment and rock anchoring beam. The numerical results reveal the dynamic failure mechanism of the surrounding rock of the underground cavern intersected by a steeply dipped fault, which can provide a reference for the seismic design.